Autonomous Underwater Vehicle (AUV) for the Study of Coastal and Upper Ocean Processes at the Woods Hole Oceanographic Institution - Gawarkiewicz, Glen; Plueddemann, Albert (2007)
We have acquired a custom REMUS Autonomous Underwater Vehicle for use in coastal and shelfbreak environments. During the past two years, we have operated the vehicle in a wide variety of oceanographic settings including the shelfbreak off New Jersey and New England, the Arctic coast near Barrow Alaska, Glove's Reef off Belize, and Vineyard Sound, Massachusetts. The vehicle capabilities have been enhanced to include an Inertial Navigation System, GPS/Iridium communications, and a SeaBird CTD. We have recently completed a study of cooling of a coastal current east of Cape Cod in winter and two manuscripts will result from this work. The vehicle was also used in the AWACS experiments off New Jersey and New England, providing the first deployment of an AUV in the shelfbreak front. The original document contains color images. All DTIC reproductions will be in black and white.